Implementation of policies regarding zakat as a deduction of taxable income: A case study in regencies and city in southern Tapanuli - Ahmad, Faisal; Hsb, Zuhdi; Kholijah, Siti (Journal of Islamic Economics Lariba, 2024)
IntroductionZakat plays a crucial role in improving the welfare of the Muslim community in Indonesia. However, Indonesian Muslims face a dual obligation: to pay both zakat and taxes. To alleviate this burden, the government implemented a policy that allows zakat to be deducted from taxable income. This policy aims to encourage zakat payers (muzakki) to distribute their zakat through official institutions such as BAZNAS. Nevertheless, zakat collection by BAZNAS in southern Tapanuli remains relatively low, necessitating an examination of the policy’s effectiveness. ObjectivesThis study aimed to evaluate the effectiveness of the zakat as a deduction of taxable income in southern Tapanuli and identify the factors affecting zakat collection through official institutions. MethodThis study employed a qualitative descriptive approach using empirical methods. Data were gathered from regulations related to zakat as a deduction of taxable income, and from observations of the performance of institutions managing zakat and taxes.ResultsThis study shows that while zakat can be applied as a deduction of taxable income, its implementation has not yet been optimal. Factors impacting the ineffectiveness of this policy include limited legal impact on payment obligations, administrative complexity, insufficient synergy between zakat and tax offices, lack of public outreach, and societal preference for directly paying zakat to recipients (mustahiq).ImplicationsThe study suggests the need to increase public outreach and synergy among institutions and simplify administrative processes to optimize zakat collection as a tax deduction. These improvements are expected to encourage broader participation in zakat distribution through official channels.Originality/NoveltyThis study contributes to the literature on the effectiveness of zakat as a tax deduction in Indonesia, particularly in southern Tapanuli. It offers insights into the challenges and opportunities of implementing this policy at the regional level.